2015
DOI: 10.4317/jced.52658
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength and debonding characteristics of metal and ceramic brackets bonded with conventional acid-etch and self-etch primer systems: An in-vivo study

Abstract: BackgroundDifferent in-vitro studies have reported various results regarding shear bond strength (SBS) of orthodontic brackets when SEP technique is compared to conventional system. This in-vivo study was designed to compare the effect of conventional acid-etching and self-etching primer adhesive (SEP) systems on SBS and debonding characteristics of metal and ceramic orthodontic brackets.Material and Methods120 intact first maxillary and mandibular premolars of 30 orthodontic patients were selected and bonded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
3
19
0
3
Order By: Relevance
“…Our study found a statistically significant difference in ARI scores between the two groups (P<0.001) in accordance with most of the studies that detected less residual adhesive on enamel after bond failure in the SEP group [6,19,30,31]. On the contrary, in some studies, bond failure in both groups occurred as an adhesive failure at the bracket surface, and the authors did not report any significant difference in ARI scores between conventional AE and SEP groups [20,21,29]. Conventional AE system takes advantage of mechanical retention in the mesh structure for bonding [7].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our study found a statistically significant difference in ARI scores between the two groups (P<0.001) in accordance with most of the studies that detected less residual adhesive on enamel after bond failure in the SEP group [6,19,30,31]. On the contrary, in some studies, bond failure in both groups occurred as an adhesive failure at the bracket surface, and the authors did not report any significant difference in ARI scores between conventional AE and SEP groups [20,21,29]. Conventional AE system takes advantage of mechanical retention in the mesh structure for bonding [7].…”
Section: Discussionsupporting
confidence: 84%
“…Although there is no definite minimum value for acceptable SBS in clinical orthodontics, various studies have reported it to be equal to 8-9 MPa [5] and 6-8 MPa [28]. Cal-Neto et al [29] and Mirzakouchaki et al [21] conducted in-vivo studies to compare the effect of SEPs and conventional AE on SBS; they obtained the same results as ours. They kept the brackets in the oral cavity for 30 days before extraction but we doubled this time frame according to their suggestion.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…En la literatura se ha investigado la infl uencia de los agentes aclaradores dentales en distintas concentraciones sobre la adhesión de los brackets (13,14,(16)(17)(18). Muchos autores han concluido que el aclaramiento dental tiene un efecto negativo sobre la adhesión de los backets causando una disminución en la fuerza de resistencia al cizallamiento (16,17,19,20).…”
Section: Discussionunclassified
“…The study of Szuhanek et al [32] shows that the mechanical treatment creates a very fine roughness on the surface area, and increases mechanical and chemical bonding between the tooth surface and the bracket base. After Mirzakouchaki et al [33], the bonding materials should penetrate into the enamel porosities and have simple manipulation and dimensional stability, but Zanarini et al [34] consider that the material should also not damage the enamel at the end of the treatment when debonding takes place. A good bonding system is literally the most important way to ensure the good adhesion of orthodontic pieces, because loose brackets during treatment mean increasing costs for both the patient and the dentist [35].…”
Section: Adhesive Remnant Index (Ari) Comparisonsmentioning
confidence: 99%